Hsp70 chaperone dynamics and molecular mechanism - Mayer, Matthias P. (Trends in biochemical sciences, 2013)
The chaperone functions of heat shock protein (Hsp)70 involve an allosteric control mechanism between the nucleotide-binding domain (NBD) and polypeptide substrate-binding domain (SBD): ATP binding and hydrolysis regulates the affinity for polypeptides, and polypeptide binding accelerates ATP hydrolysis. These data suggest that Hsp70s exist in at least two conformational states. Although structural information on the conformation with high affinity for polypeptides has been available for several years, the conformation with an open polypeptide binding cleft was elucidated only recently. In addition, other biophysical studies have revealed a more dynamic picture of Hsp70s, shedding light on the molecular mechanism by which Hsp70s assist protein folding. In this review recent insights into the structure and mechanism of Hsp70s are discussed.